Analysis of capital structure in power companies in Asian economies - Shrestha, Ashish; Venkatesh, Sundar; Badir, Yuosre; Zimmermann, Willi; Asian Institute of Technology Fellowship (2019)
Purpose - The purpose of this research is to examine and analysis of debt, sources of debt and differences in debt. It focuses on mainly cross country and cross company reasons of debt. Methodology - A synthetic credit ratings were done by gathering data from company's annual report. Debt to equity ratios were compared of each country with other country, and each company with other company. Furthermore, a multiple regression s done in order to find out the strength of dependency of each independent variable with capital structure. The variables used for the research are Tax rate, Interest rate, Market Capitalization, ROE, ROA, Size of the energy production and Source of energy. Indebt case study is done for the companies that showed unique characteristics in their debt to equity ratio. (For example: having extremely high debt or having no debt at all). Findings - Debt to equity ratio are significantly impacted by Tax rates, Interest rates, Financial Market Development, size of the firm, ROE, ROA, and type of company. However, besides the determining factors, it is known that more secured a business firm is by government, more the company borrows. Large firms do not necessarily mean they have larger debt, unless it is secured by government. In addition, the type of business also matters when borrowing debt. More the source IS renewable, easier to get the debt in low cost. Implication - This research will be helpful to financials of power companies who prefers debt financing. It explains how a firm might be able to increase debt financing without increasing the risk.
A research study submitted in partial fulfillment of the requirements for the degree of Master of Business Administration
Research Studies Project Report (M.B.A.) - Asian Institute of Technology, 2019
Keywords: Capital -- Asian; Corporations -- Finance -- Asian